Online-Based Transportation: Is It Legal? - Yoga Sugama Ali Fhatnur (Universitas Muhammadiyah Sidoarjo, 2018)
This study aims to observe the legality of online-based transportation in Indonesia. As a law-abiding State, all the activities of the nation and the state shall be based on the regulation of law. However, on the other hand, the type of online-based transportation has potential to develop problems and also to trigger the pros and cons that exist in the community.This cons consider that the type of online-based transportation is illegal because it is not in accordance with the provisions of the applicable Law on Road, Traffic and Transportation, which states that business licensesare required for companies to have legal status. This is because the process of conducting conveyance consists series of actions to carry passengers, such as collecting fees which must be supported by a business license and a definite operating license. To be able to carry out transportation activities, the legal entity concerned must have an approbate business license.